2006
DOI: 10.1080/01485010600666953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Chromatin Damage on Fertilization Ratio and Embryo Quality Post-Icsi

Abstract: A total of 56 semen samples was collected from men in the ICSI program. The female partners of all men were under 35 years of age. Sperm chromatin integrity was evaluated by staining the spermatozoa with acridine orange. > 56% red fluorescence was taken as abnormal chromatin status. A significant negative association was found between the percentage of sperm with DNA fragmentation and fertilization rate. Increased red fluorescence indicated impaired fertilization outcome. Good quality embryo rates were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Although preservation of sperm membranes and motility are important measures of sperm quality, they may not reveal the changes in DNA. The analysis of DNA fragmentation (sDF) has explained the infertility of individuals with apparently normal seminograms [24,25]. This approach is particularly interesting because DNA fragmentation correlates poorly with classical parameters of semen quality [26] as also occurs in donkey sperm [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although preservation of sperm membranes and motility are important measures of sperm quality, they may not reveal the changes in DNA. The analysis of DNA fragmentation (sDF) has explained the infertility of individuals with apparently normal seminograms [24,25]. This approach is particularly interesting because DNA fragmentation correlates poorly with classical parameters of semen quality [26] as also occurs in donkey sperm [27].…”
Section: Discussionmentioning
confidence: 99%
“…Increased red fluorescence indicated impaired fertilization outcome, and good quality embryo rates were significantly lower in the group with high sperm DNA fragmentation. Chromatin damage precedes the loss of fertilization potential and poor embryo quality, resulting in pregnancy loss (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to evaluate relationships between abnormal sperm DNA detected by AO and adverse outcomes in both in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), such as lower implantation rates and higher pregnancy loss. It has even been suggested that abnormal sperm DNA may affect offspring (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%